2016
DOI: 10.3746/pnf.2016.21.3.197
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and In vivo Anti-Helicobacter pylori Activities of Centella asiatica Leaf Extract

Abstract: Helicobacter pylori infection is associated with an increased risk of developing upper gastrointestinal tract diseases. However, treatment failure is a major cause of concern mainly due to possible recurrence of infection, the side effects, and resistance to antibiotics. The aim of this study was to investigate the activities of Centella asiatica leaf extract (CAE) against H. pylori both in vitro and in vivo. The minimum inhibitory concentrations (MICs) against 55 clinically isolated strains of H. pylori were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The mechanisms involved were as follows: the reduction of related inflammation factors (IL−1β ↓, IL−2 ↓, IL−6 ↓, IL−10 ↓, IL−12 ↓, and TNF−α ↓) and the increase in the level of antioxidant stress factors (SOD ↑, CAT ↑, and GPx ↑). Furthermore, evidence showed that C. asiatica could also reduce MDA and COX-2 levels, thereby ameliorating gastric mucosal damage ( Choi et al, 2016 ; Zheng et al, 2016a ; Zheng et al, 2016b ; Intararuchikul et al, 2019 ; Wannasarit et al, 2019 ). The pharmacological effect of asiatic acid is mainly reflected in the improvement in liver fibrosis and acute pancreatitis.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms involved were as follows: the reduction of related inflammation factors (IL−1β ↓, IL−2 ↓, IL−6 ↓, IL−10 ↓, IL−12 ↓, and TNF−α ↓) and the increase in the level of antioxidant stress factors (SOD ↑, CAT ↑, and GPx ↑). Furthermore, evidence showed that C. asiatica could also reduce MDA and COX-2 levels, thereby ameliorating gastric mucosal damage ( Choi et al, 2016 ; Zheng et al, 2016a ; Zheng et al, 2016b ; Intararuchikul et al, 2019 ; Wannasarit et al, 2019 ). The pharmacological effect of asiatic acid is mainly reflected in the improvement in liver fibrosis and acute pancreatitis.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Zheng et al [ 82 ] using an extract of C. asiatica obtained by the maceration method found that at 2 mg/mL, it inhibited the growth of Helicobacter pylori by the agar well diffusion method; the MIC against the strains tested ranged from 0.125 to 8 mg/mL. Methanol extract obtained by the maceration method showed a broad spectrum of antimicrobial activity using the agar diffusion method against both Gram-positive and -negative bacteria, with the zones of inhibition ranging from 9 to 29 mm and the MIC ranging from 1.25 to >10 mg/mL [ 76 ].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Figure 10 shows the effectiveness in vivo of C. asiatica extracts obtained using maceration in reducing H. pylori gastric mucosal colonization in a C57BL/6 mouse model. The optimum concentration was 50 mg/kg after oral administration once daily for three weeks [ 82 ].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The extracts inhibitory activities against H. pylori was also confirmed by the H pylori count in gastric biopsy culture, where the decrease in bacterial population was observed from samples treated with both extracts (cold water and ethanol) and clarithromycin. Several studies have also reported that extracts from several other plants, such as Allium sativum [15], Centella asiatica leaf [16], Aframomum pruinosum seeds [17], Calophyllum brasiliense Camb. [34], turmeric [35] and garlic powder and oil [36] have activities against H. pylori.…”
Section: Discussionmentioning
confidence: 99%